Rising Net Shortwave Radiation and Land Surface Temperature Drive Snow Cover Phenology Shifts Across the Mongolian Plateau During the 2000–2022 Hydrological Years - Xiaona Chen; Shiqiu Lin (Remote Sensing, 2025)
Snow cover phenology (SCP) serves as a critical regulator of hydrological cycles and ecosystem stability across the Mongolian Plateau (MP). Despite its importance, the spatiotemporal patterns of SCP and their climatic drivers remain poorly quantified, constrained by persistent gaps in satellite snow cover observations. Leveraging a high-resolution (500 m) daily gap-filled Moderate Resolution Imaging Spectroradiometer (MODIS) snow cover dataset combined with reanalysis climate datasets, we systematically quantified SCP dynamics and identified the dominant controls during the 2000–2022 hydrological years using trend analysis and ridge regression. Our results reveal a significant divergence in SCP parameters: snow end dates (De) advanced markedly across the entire plateau (0.29 days yr−1, p < 0.01), accounting for 90.39% of SCP anomalies. In contrast, snow onset date (Do) exhibited unnoticeable changes, explaining 9.58% of SCP changes. Attribution analysis demonstrates that 47.72% of De variability stems from increased net shortwave radiation (+0.38 Wm−2 yr−1) and rising temperatures (+0.06 °C yr−1) during the melting season, with net shortwave radiation exerting stronger control (R2 = 0.73) than temperature (R2 = 0.63). This study establishes the first continuous, high-resolution SCP climatology for the MP, providing mechanistic insights into cryosphere–atmosphere interactions that inform adaptive water resource strategies for climate-vulnerable arid ecosystems in this region.